INVESTIGATION OF THREATS AND VULNERABILITY IN THE CRITICAL INFRASTRUCTURE OF TECHNOGENIC OBJECTS AND SYSTEMS - Олег Евгеньевич Федорович; Наталия Валентиновна Еременко; Вадим Алексеевич Пуйденко (Авіаційно-космічна техніка та технологія, 2017)
The problem of research of threats in critical infrastructures (CI) of technical objects and systems (TOS) is formulated and solved. The following methods are proposed: choosing an efficient option for carrying out the measures to neutralize the threats and minimize the damage in case of a threat. The structure of the agent simulation model to investigate the impact of threats and vulnerabilities in CI TOS is developed. The proposed approach allows eliminating the risks associated with the impact of aggressive external influences on the infrastructure of technogenic objects in order to ensure their normal functioning under conditions of moral and physical aging.